2016
DOI: 10.4103/1735-1995.181983
|View full text |Cite
|
Sign up to set email alerts
|

Clinical teaching with emotional intelligence: A teaching toolbox

Abstract: Background:Emotional intelligence (EI) helps humans to perceive their own and others’ emotions. It helps to make better interpersonal communication that consequently leads to an increase in everyday performance and professional career. Teaching, particularly teaching in the clinical environment, is among the professions that need a high level of EI due to its relevance to human interactions.Materials and Methods:We adopted EI competencies with characteristics of a good clinical teacher. As a result, we extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Emotional intelligence (EI) plays an important role in medicine and medical education. 1 - 3 EI is defined as the ability to perceive emotions, access and generate emotions, understand emotions, and reflectively regulate it for promoting emotional and intellectual growth. 2 It denotes the cooperative mixture between intelligence and emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional intelligence (EI) plays an important role in medicine and medical education. 1 - 3 EI is defined as the ability to perceive emotions, access and generate emotions, understand emotions, and reflectively regulate it for promoting emotional and intellectual growth. 2 It denotes the cooperative mixture between intelligence and emotions.…”
Section: Introductionmentioning
confidence: 99%
“…EI has been recognized as an essential trait for medical students and health care providers. 1 , 6 It can be considered as one predictor of good performance and better quality of care delivered to patients. Medical students, as future practitioners, need to have sound EI for having more effective communication and empathy with their patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the application of emotional intelligence, ie, techniques and insights that help humans perceive their own and others’ emotions, in teaching has led to improvement in clinical teachers’ performances 4. Application of emotional intelligence could also avoid “negative emotional reactions such as denial and defense,” experienced by some of the teachers in Jamshidian et al’s study,1 and allow clinical teachers to reflect on feedback content objectively.…”
Section: Dear Editormentioning
confidence: 99%
“…There were various studies that confirmed the fact of the influence of emotional intelligence of teachers on their work (Dolev & Leshem, 2016, 2017Gilar-Corbi et al, 2018;Kassim et al, 2016;Omid et al, 2016;Zurita-Ortega et al, 2018).…”
Section: Introductionmentioning
confidence: 97%